Impact of Decentralization in East Kalimantan Province on Mineral and Coal Mining Policy - Risal, Semuel; Zauhar, Soesilo; Sarwono, Sarwono; Hermawan, Hermawan (JPAS (Journal of Public Administration Studies), 2020)
This study analyzes the relationship between the decentralization policy in East Kalimantan Province and coal mining, using a literature study. The finding shows evidence that there is a mixed impact between the decentralization and mineral and mining sectors. The decentralization policy has provided opportunities for local governments to manage and utilize their natural resources independently. Decentralization in the mining sector brings positive impacts on economic security, as indicated by an increase in the East Kalimantan provinces human development index as of 2016 reaching 74.59. Decentralization would therefore be good for economic growth and poor for basic services such as education and health and the occurrence of landscape changes that lead to environmental damage.